Expansion/shrinkage history of the Paratethys Sea during the Eocene: New insights from eolian Red Clay records in the Altyn Mountains, northern China - Guo, Benhong; Nie, Junsheng; Li, Jianxing; Xiao, Wenjiao; Pan, Feng (Frontiers in Earth Science, 2022)
Uplift of the Tibetan Plateau, expansion/shrinkage of the Paratethys Sea, and global climate are three major forcings for central-east Asian climatic and environmental variations during the Cenozoic. However, knowledge of expansion/shrinkage history of the Paratethys Sea is much less well known in comparison with the other two forcings. Here, we present a first multiple-parameter environmental magnetic and diffuse reflectance spectroscopy study of the Eocene eolian Red Clay deposits (~51-40 Ma) in the Xorkol Basin of the northeastern Tibetan Plateau, which is near the easternmost maximum boundary of the Eocene Paratethys Sea. The first detailed Eocene expansion/shrinkage history of the Paratethys Sea was reconstructed based on the hematite content of the Eocene Red Clay, which shows remarkable consistency with the previous low-resolution Paratethys Sea paleowater depth record in the southwestern Tarim Basin. These results demonstrate that the Paratethys Sea experienced a three-stage (shrinkage-expansion-shrinkage) evolution between ~51 and 40 Ma, with boundaries at ~46.2 and 42 Ma. Superimposed on this framework, the Paratethys Sea experienced four times of rapid shrinkages at the expansion phase (shows 400-kyr cycles) during ~44-42 Ma modulated by eccentricity forcings. These new results are of great significance to evaluate respective role of Tibetan uplift, global climate, and Paratethys Sea area variations in Asian climate and environmental change over the Eocene.